USE OF CITRUS AS SUBSTRATE FOR SEMI-CAPTIVITY BREEDING OF Hermetia illucens "BLACK SOLDIER FLY" IN LORETO, PERU - MURRIETA MOREY, Germán Augusto (2023)
In the rearing of native fish of the Peruvian Amazon such as Colossoma macropomum, Piaractus brachypomus, Brycon amazonicus, Prochilodus nigricans and Arapaima gigas, balanced feed is used, in whose formulation fishmeal and other non‑local inputs predominate. This makes its acquisition more expensive and difficult, mainly by rural Amazonian producers who are far from the urban area. Worldwide, there are experiences of alternatives for raising fish based on the use of vegetables, fruits and insects, taking advantage of the biological diversity of the environment. Thus, the use of insect larvae constitutes a promising alternative for the aquaculture sector on a global scale. The present study shows the semi‑captivity breeding of Hermetia illucens "black soldier fly" using organic waste (citrus) collected from urban and rural areas, highlighting the use of orange bagasse and grapefruit . In this way, using the circular economy principle, live larvae and soldier fly meal were obtained to be used as an alternative to feed commercially important fish. As a final product of the rearing of the larvae, an organic compost ideal for agroforestry systems was obtained. This study shows a cheap, accessible and environmentally friendly methodology for raising black soldier fly in semi‑captivity in the region of Loreto by using citrus from the urban and rural area.